Biobr / bi2fe4o9 heterojunction composite photocatalyst and preparation method and application thereof

CN122999228APending Publication Date: 2026-10-30ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611220303.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]本发明的第一个目的是提供一种BiOBr/Bi2Fe4O9异质结复合光催化剂的制备方法,以解决单一组分光催化材料载流子复合率高的问题

Benefits of technology

本发明的BiOBr/Bi2Fe4O9异质结复合光催化剂的制备方法,采用共沉淀-水热法先合成Bi2Fe4O9前驱体,再通过溶剂热法在其表面原位生长BiOBr纳米片,形成BiOBr/Bi2Fe4O9的Z型异质结复合体系。该BiOBr/Bi2Fe4O9异质结复合光催化剂的制备方法通过原位生长实现两相界面紧密接触,避免了宏观相分离,在界面处形成化学键合,确保异质结的高效构建,利用乙二醇作为溶剂和形貌调控剂,促进BiOBr纳米花状微球的形成,从而显著增大比表面积和活性位点密度。该BiOBr/Bi2Fe4O9异质结复合光催化剂的制备方法反应条件温和、操作简便、普适性强,为高效降解对苯二胺类新污染物提供了材料基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999228A_ABST
    Figure CN122999228A_ABST
Patent Text Reader

Abstract

The application discloses a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst and a preparation method and application thereof, and belongs to the technical field of photocatalytic materials. The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst comprises the following steps: dissolving a first bismuth source and an iron source in a solvent, drying after a first reaction to obtain a Bi2Fe4O9 precursor; dispersing the obtained Bi2Fe4O9 precursor in an alcohol solvent, adding a second bismuth source and a bromine source, and performing a second reaction to obtain the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst. The preparation method of the BiOBr / Bi2Fe4O9 heterojunction photocatalyst adopts a co-precipitation-hydrothermal method to first synthesize a Bi2Fe4O9 precursor, and then grows BiOBr nanosheets on the surface of the Bi2Fe4O9 precursor through a solvothermal method to form a Z-type heterojunction composite system of BiOBr / Bi2Fe4O9. The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst can be used as a visible light response photocatalyst to degrade new pollutants of p-phenylenediamine represented by 6PPD in water, and the removal rate of 6PPD of 10 mg / L can reach 91% within 60 min under visible light irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalytic materials technology, specifically relating to a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, its preparation method, and its application. Background Technology

[0002] With the rapid development of modern transportation industry, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) and its highly toxic conversion product 6PPD-Q carried by tire wear particles (TWPs) are frequently detected in aquatic environments, posing a serious threat to ecosystems and public health. Photocatalysis technology, due to its ability to generate highly reactive oxidizing species using solar energy at ambient temperature and pressure to achieve efficient degradation of pollutants, has become a research hotspot in the field of trace new pollutant treatment. However, single semiconductor photocatalysts (such as TiO2 and BiOBr) still face bottlenecks in practical applications, such as high recombination rates of photogenerated carriers and insufficient visible light response, making it difficult to meet the requirements for efficient degradation of 6PPD.

[0003] Bismuth-based heterojunction catalysts have shown great research potential in environmental remediation in recent years due to their unique band structure and excellent visible light response. In the photocatalytic degradation of organic pollutants, BiOBr-based heterojunction catalysts effectively suppress carrier recombination through interfacial charge transfer, exhibiting superior performance in the degradation of pollutants such as antibiotics and dyes. Bi₂Fe₄O₉, as a narrow-bandgap bismuth-based semiconductor, has been proven to have good activity in the photocatalytic degradation of organic compounds such as phenol and rhodamine B due to its ferroelectric properties and visible light absorption. When BiOBr and Bi₂Fe₄O₉ are combined to form a heterojunction, a Z-type or S-type charge transfer mechanism can be formed, achieving efficient spatial separation of photogenerated electron-hole pairs while retaining their respective strong redox capabilities, theoretically enabling the effective degradation of 6PPD. However, current synthesis methods for bismuth-based heterojunction catalysts generally have some shortcomings. Achieving close interfacial contact between the two components, avoiding macroscopic phase separation, and further simplifying the synthesis process remain urgent problems to be solved in the construction of bismuth-based heterostructures.

[0004] In existing technologies, there are many methods for preparing bismuth-based photocatalysts, mainly including strategies such as homogeneous structure construction and heterogeneous structure construction, but these methods have the following problems: The invention patent with publication number CN121082296A discloses the preparation and application of a coordination-assisted oxygen vacancy-regulated 2D / 2D black BiOBr / white BiOBr homojunction catalyst. This preparation method utilizes EDTA-2Na as a coordination-reduction bifunctional regulator, controlling its interaction with Bi... 3+This method achieves in-situ construction of S-type homojunctions with controllable oxygen vacancy concentrations by adjusting the molar ratio of EDTA-2Na, thereby improving visible light absorption and the separation efficiency of photogenerated carriers. However, this method requires precise control of the amount of EDTA-2Na used, the oxygen vacancy concentration regulation depends on the coordination system, and a hydrothermal reaction at 180 °C for 8 h is required, resulting in high energy consumption. Furthermore, the formation of the homojunction interface is sensitive to process parameters such as precursor concentration and stirring conditions, and batch-to-batch reproducibility needs further improvement, which is not conducive to large-scale preparation.

[0005] Chinese patent application CN122057538A discloses a method for preparing and applying a BiOBr / TiO2 composite material. The method involves first preparing a TiO2 nanorod array, then loading BiOBr nanosheets onto its surface using a solvothermal method to obtain a composite photocatalytic material with a heterojunction structure. While this method can improve the photocatalytic performance of the composite material, its preparation still requires a high temperature and a long solvothermal reaction time, resulting in high energy consumption and preparation costs. Furthermore, the uniformity of BiOBr loading on the TiO2 surface and the degree of contact between the two phases are still insufficient, limiting the effective separation and transport of photogenerated carriers, and there is still room for further improvement in catalytic performance.

[0006] Therefore, there is an urgent need to provide a simple and mild method for preparing bismuth-based heterojunction catalysts, so that the obtained BiOBr / Bi2Fe4O9 heterojunction catalysts have close interfacial contact, solve the problem of high carrier recombination rate in single-component photocatalytic materials, and enhance the visible light absorption capacity and structural stability of the catalysts to achieve efficient and rapid degradation of 6PPD. Summary of the Invention

[0007] The first objective of this invention is to provide a method for preparing a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst to solve the problem of high carrier recombination rate in single-component photocatalytic materials.

[0008] The second objective of this invention is to provide a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst.

[0009] The third objective of this invention is to provide an application of a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in the catalytic degradation of novel pollutants such as phenylenediamine in water.

[0010] The fourth objective of this invention is to provide a method for degrading novel pollutants such as p-phenylenediamine in water.

[0011] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, comprising the following steps: S1: Dissolve the first bismuth source and iron source in a solvent, carry out the first reaction, and then dry to obtain the Bi2Fe4O9 precursor; S2: The Bi2Fe4O9 precursor obtained in S1 is dispersed in an alcohol solvent, and a second bismuth source and a bromine source are added to carry out a second reaction to obtain a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst.

[0012] Furthermore, in S1, the first bismuth source comprises bismuth nitrate pentahydrate, the iron source comprises ferric nitrate nonahydrate, the molar ratio of the first bismuth source to the iron source is 1:(1.5-2.5); the molar volume ratio of the first bismuth source to the solvent is 1 mmol:(30-50) mL; and the solvent is water.

[0013] Furthermore, S1, after dissolving the first bismuth source and the iron source in the solvent, also includes adding an alkaline solution to adjust the pH to 10 and continuing stirring for 1 h. The alkaline solution includes a sodium hydroxide solution with a concentration of 2-7 mol / L. The temperature of the first reaction is 160-180 °C and the time is 12 h. The drying temperature is 60 °C and the time is 12 h.

[0014] Furthermore, the alcohol solvent in S2 includes ethylene glycol; the bromine source includes at least one of potassium bromide, sodium bromide, or ammonium bromide; and the mass-to-volume ratio of the Bi2Fe4O9 precursor obtained in S1 to the alcohol solvent is 0.15 g: 30 mL.

[0015] Furthermore, ethylene glycol acts as both a solvent and a morphology modifier, enabling BiOBr to form a nanoflower-like microsphere structure.

[0016] Furthermore, the bromine source is preferably potassium bromide.

[0017] Furthermore, in S2, the second bismuth source comprises bismuth nitrate pentahydrate; the molar ratio of the second bismuth source to the bromine source is 1:1; each (0.1–0.2) g of the Bi2Fe4O9 precursor corresponds to (0.05–1.0) mmol of the second bismuth source; the temperature of the second reaction is 160 °C, and the time is 12 h.

[0018] Secondly, the present invention provides a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst as described above. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, tetragonal BiOBr nanosheets are discontinuously attached to the surface of orthorhombic Bi2Fe4O9 particles to form a Z-shaped heterojunction. The BiOBr nanosheets exist in the form of nanoflower-like microspheres, and the thickness of the BiOBr nanosheets is 10-20 nm. The particle size of the Bi2Fe4O9 particles is 200-500 nm. The Bi2Fe4O9 particles and the BiOBr nanosheets are bonded by Bi-O-Fe chemical bonds. The mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst is 10-75%.

[0019] Furthermore, the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst is preferably 35%.

[0020] Furthermore, in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, Bi2Fe4O9 serves only as a substrate for heterogeneous nucleation and does not participate in dissolution. The generation of BiOBr is entirely due to the heterogeneous nucleation and growth of added ions on the surface of Bi2Fe4O9 via a solvothermal reaction.

[0021] Furthermore, the BiOBr is assembled from nanosheets, which are loose and porous, forming point-to-surface or surface-to-surface contact with Bi2Fe4O9 particles, resulting in a larger specific surface area and more active sites.

[0022] Thirdly, the present invention provides an application of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst described above in the catalytic degradation of new p-phenylenediamine pollutants in water, wherein the new p-phenylenediamine pollutants include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine.

[0023] Fourthly, the present invention provides a method for degrading new pollutants of p-phenylenediamine in water, comprising the following steps: adding the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst as described in claim 6 to the water containing the new pollutants of p-phenylenediamine, and carrying out a photocatalytic reaction under visible light conditions.

[0024] Furthermore, the novel pollutant of p-phenylenediamine includes N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine; the temperature of the photocatalytic reaction is 23–27 °C; the light source for the visible light is a 300 W xenon lamp, and the wavelength of the visible light is >420 nm.

[0025] Furthermore, 20–50 mg of BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst is added to every 100 mL of the water to be treated; the concentration of p-phenylenediamine-like new pollutants in the water to be treated is 10 mg / L.

[0026] The beneficial effects of this invention are: The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention involves first synthesizing a Bi2Fe4O9 precursor via a coprecipitation-hydrothermal method, and then growing BiOBr nanosheets in situ on its surface using a solvothermal method to form a Z-shaped heterojunction composite system of BiOBr / Bi2Fe4O9. This preparation method achieves close contact between the two phases through in-situ growth, avoiding macroscopic phase separation and forming chemical bonds at the interface, ensuring efficient construction of the heterojunction. Ethylene glycol is used as a solvent and morphology modifier to promote the formation of BiOBr nanoflower-like microspheres, thereby significantly increasing the specific surface area and active site density. The preparation method of this BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst has mild reaction conditions, is simple to operate, and has strong versatility, providing a material basis for the efficient degradation of novel pollutants such as p-phenylenediamine.

[0027] The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention uses ethylene glycol solvent, with a near-neutral pH, and the reaction conditions are mild and safe. Furthermore, the mass fraction of BiOBr can be precisely controlled by adjusting the amount of Bi2Fe4O9 precursor added, thereby optimizing the component ratio.

[0028] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of this invention possesses a unique heterojunction structure. Bi2Fe4O9 particles and BiOBr nanoflower-like microspheres are in close contact at the interface, with uniform elemental distribution and interfacial chemical bonding. This BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst follows a Z-type charge transfer mechanism, effectively promoting the spatial separation of photogenerated carriers while retaining the strongest redox capabilities of both components, thereby generating abundant reactive oxygen species and achieving efficient degradation of 6PPD. Quenching experiments confirm that photogenerated holes and superoxide radicals are the dominant active species.

[0029] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of this invention can be used as a visible light-responsive photocatalyst for degrading new pollutants such as p-phenylenediamine, represented by 6PPD, in water. Under visible light irradiation, the removal rate of 6PPD at an initial concentration of 10 mg / L can reach 91% within 60 min. The apparent rate constant during the photocatalytic degradation process is 4 to 6 times that of pure-phase BiOBr and pure-phase Bi2Fe4O9, respectively. This BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst maintains high degradation efficiency even after multiple cycles, and its performance is optimal under neutral conditions, matching the pH range of natural water bodies. This is beneficial for the deep removal of trace pollutants and has unique advantages in practical water treatment. The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst maintains high degradation efficiency even after multiple cycles, exhibiting excellent catalytic activity and stability, and has broad application prospects in the field of water treatment. Attached Figure Description

[0030] Figure 1 This is a process flow diagram of the preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention; Figure 2 The image shows a scanning electron microscope (SEM) image of the pure-phase BiOBr nanoflower-like microspheres from Comparative Example 1. Figure 3 The image shows a scanning electron microscope (SEM) image of pure-phase Bi2Fe4O9 particles from Comparative Example 2. Figure 4 This is a scanning electron microscope image of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst from Example 1. Figure 5 X-ray diffraction spectra of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1, the pure phase BiOBr nanospheres of Comparative Example 1, and the pure phase Bi2Fe4O9 particles of Comparative Example 2. Figure 6 The active species quenching test and removal rate comparison of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst for the degradation of 6PPD in Example 1 are shown in Figure A, which is a curve of 6PPD removal rate changing with time under different quenching agents, and Figure B is a comparison of 6PPD removal rate after 60 min of reaction under different quenching agents. Figure 7 This is a comparison chart of the removal rates of 6PPD in the methods for degrading new pollutants such as p-phenylenediamine in water in Examples 7 and 9-12. Figure 8 This is a comparison chart of the removal rates of 6PPD in the methods for degrading new pollutants such as p-phenylenediamine in water in Examples 7 and Comparative Examples 5-6; Figure 9This is a comparison chart of the removal rates of 6PPD by the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 1 under different initial pH conditions. Figure 10 This is a comparison of the visible light catalytic degradation efficiency of 6PPD by different precursor composite systems. Detailed Implementation

[0031] In the following examples, 6PPD is used as a representative target pollutant of new p-phenylenediamine pollutants to verify the effectiveness of the method of the present invention for degrading new p-phenylenediamine pollutants in water.

[0032] In the following examples, the concentration of 6PPD was determined using high performance liquid chromatography (HPLC) at a detection wavelength of 254 nm, and the degradation rate was calculated according to Formula I.

[0033] Degradation rate = (C0 - C) t ) / C0×100 %, Formula I.

[0034] In Equation I, C0 is the initial concentration after adsorption equilibrium, C t The concentration at time t is the concentration at which the reaction occurs.

[0035] The following will provide further details with reference to embodiments of the present invention.

[0036] Example 1 The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 1 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. While stirring, 2.0 mol / L NaOH solution was slowly added dropwise to the mixed solution to adjust the pH to 10, and stirring was continued for 1 h to obtain a suspension containing a brown precipitate. The suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the Bi2Fe4O9 precursor.

[0037] 0.15 g of the obtained Bi₂Fe₄O₉ precursor was weighed and dispersed in 30 mL of ethylene glycol. The mixture was sonicated for 30 min, followed by the addition of 0.26 mmol of Bi(NO₃)₃·5H₂O and 0.26 mmol of KBr. The mixture was stirred for another 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reactor and subjected to a solvothermal reaction at 160 °C for 12 h. After the reaction, the reaction product was cooled, centrifuged, and then washed three times each with deionized water and ethanol. The product was then dried at 60 °C for 12 h to obtain the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst.

[0038] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1 was prepared by the same method as the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1, the thickness of the BiOBr nanosheets was 10-20 nm, the particle size of the Bi2Fe4O9 particles was 200-500 nm, and the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1 was 35%.

[0039] The SEM and XRD patterns of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 1 are shown below. Figure 4 and Figure 5 As shown, the XRD pattern shows sharp characteristic peaks that match the standard cards for tetragonal BiOBr (JCPDS No. 09-0393) and orthorhombic Bi2Fe4O9 (JCPDS No. 25-0090), respectively. It also exhibits characteristic diffraction peaks of both tetragonal BiOBr and orthorhombic Bi2Fe4O9, with sharp peak shapes and no impurity peaks, indicating that the two phases coexist and have good crystallinity.

[0040] from Figure 4 As can be seen, Bi₂Fe₄O₉ is granular with a particle size of 200–500 nm. Its surface is discontinuously attached with BiOBr nanosheets of 10–20 nm thickness, forming a discrete heterojunction interface. The BiOBr nanosheets exist in the form of nanoflower-like microspheres, and the interface between the two phases is clearly visible, with a large number of exposed Bi₂Fe₄O₉ surfaces and BiOBr edges, which is beneficial for exposing active sites.

[0041] In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1, the original morphology and lattice of Bi2Fe4O9 particles are completely preserved. BiOBr nanoflower-like microspheres grow on the surface of Bi2Fe4O9 particles through physical adsorption and chemical bonding. Bi2Fe4O9 particles and BiOBr nanoflower-like microspheres are in close contact at the interface, with uniform element distribution and a clear heterojunction interface without etching damage.

[0042] Example 2 The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 2 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. While stirring, 2.0 mol / L NaOH solution was slowly added dropwise to the mixed solution to adjust the pH to 10, and stirring was continued for 1 h to obtain a suspension containing a brown precipitate. The suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the Bi2Fe4O9 precursor.

[0043] 0.20 g of the obtained Bi₂Fe₄O₉ precursor was weighed and dispersed in 50 mL of ethylene glycol. The mixture was sonicated for 30 min, followed by the addition of 0.16 mmol of Bi(NO₃)₃·5H₂O and 0.16 mmol of KBr. The mixture was stirred for another 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reactor and subjected to a solvothermal reaction at 160 °C for 12 h. After the reaction, the reaction product was cooled, centrifuged, and then washed three times each with deionized water and ethanol. The product was then dried at 60 °C for 12 h to obtain the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst.

[0044] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 2 was prepared by the same method as the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 2. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 2, the thickness of the BiOBr nanosheets was 10-20 nm, the particle size of the Bi2Fe4O9 particles was 200-500 nm, and the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 2 was 20%.

[0045] Example 3 The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 3 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. While stirring, 2.0 mol / L NaOH solution was slowly added dropwise to the mixed solution to adjust the pH to 10, and stirring was continued for 1 h to obtain a suspension containing a brown precipitate. The suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the Bi2Fe4O9 precursor.

[0046] 0.10 g of the obtained Bi₂Fe₄O₉ precursor was weighed and dispersed in 50 mL of ethylene glycol. The mixture was sonicated for 30 min, followed by the addition of 0.33 mmol of Bi(NO₃)₃·5H₂O and 0.33 mmol of KBr. The mixture was stirred for another 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL high-pressure reactor lined with polytetrafluoroethylene (PTFE) and subjected to a solvothermal reaction at 160 °C for 12 h. After the reaction was complete, the reaction product was cooled, centrifuged, and then washed three times each with deionized water and ethanol. The product was then dried at 60 °C for 12 h to obtain the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst.

[0047] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 3 was prepared by the same method as the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 3. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 3, the thickness of the BiOBr nanosheets was 10-20 nm, the particle size of the Bi2Fe4O9 particles was 200-500 nm, and the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 3 was 50%.

[0048] Example 4 The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 4 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. While stirring, 2.0 mol / L NaOH solution was slowly added dropwise to the mixed solution to adjust the pH to 10, and stirring was continued for 1 h to obtain a suspension containing a brown precipitate. The suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the Bi2Fe4O9 precursor.

[0049] 0.15 g of the obtained Bi₂Fe₄O₉ precursor was weighed and dispersed in 30 mL of ethylene glycol. The mixture was sonicated for 30 min, followed by the addition of 0.05 mmol of Bi(NO₃)₃·5H₂O and 0.05 mmol of KBr. The mixture was stirred for another 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL high-pressure reactor lined with polytetrafluoroethylene (PTFE) and subjected to a solvothermal reaction at 160 °C for 12 h. After the reaction, the reaction product was cooled, centrifuged, and then washed three times each with deionized water and ethanol. The product was then dried at 60 °C for 12 h to obtain the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst.

[0050] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 4 was prepared by the same method as the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 4. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 4, the thickness of the BiOBr nanosheets was 10-20 nm, the particle size of the Bi2Fe4O9 particles was 200-500 nm, and the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 4 was 10%.

[0051] Example 5 The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 5 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. While stirring, 2.0 mol / L NaOH solution was slowly added dropwise to the mixed solution to adjust the pH to 10, and stirring was continued for 1 h to obtain a suspension containing a brown precipitate. The suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the Bi2Fe4O9 precursor.

[0052] 0.20 g of the obtained Bi₂Fe₄O₉ precursor was weighed and dispersed in 30 mL of ethylene glycol. The mixture was sonicated for 30 min, followed by the addition of 0.22 mmol of Bi(NO₃)₃·5H₂O and 0.22 mmol of KBr. The mixture was stirred for another 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reactor and subjected to a solvothermal reaction at 160 °C for 12 h. After the reaction, the reaction product was cooled, centrifuged, and then washed three times each with deionized water and ethanol. The product was then dried at 60 °C for 12 h to obtain the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst.

[0053] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 5 was prepared by the same method as the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 5. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 5, the thickness of the BiOBr nanosheets was 10-20 nm, the particle size of the Bi2Fe4O9 particles was 200-500 nm, and the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 5 was 25%.

[0054] Example 6 The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 6 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. While stirring, 2.0 mol / L NaOH solution was slowly added dropwise to the mixed solution to adjust the pH to 10, and stirring was continued for 1 h to obtain a suspension containing a brown precipitate. The suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the Bi2Fe4O9 precursor.

[0055] 0.10 g of the obtained Bi₂Fe₄O₉ precursor was weighed and dispersed in 30 mL of ethylene glycol. The mixture was sonicated for 30 min, followed by the addition of 1.0 mmol of Bi(NO₃)₃·5H₂O and 1.0 mmol of KBr. The mixture was stirred for another 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reactor and subjected to a solvothermal reaction at 160 °C for 12 h. After the reaction, the reaction product was cooled, centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst.

[0056] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 6 was prepared by the same method as the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 6. In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 6, the thickness of the BiOBr nanosheets was 10-20 nm, the particle size of the Bi2Fe4O9 particles was 200-500 nm, and the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 6 was 75%.

[0057] Example 7 The method for degrading new pollutants such as p-phenylenediamine in water as described in Example 7 includes the following steps: Add 50 mL of a 10 mg / L 6PPD aqueous solution to a 100 mL quartz beaker, then add 25 mg of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst from Example 1. Stir magnetically in the dark for 30 min to reach adsorption-desorption equilibrium. Then, turn on a xenon lamp with a 420 nm cutoff filter (300 W power) and conduct the photocatalytic reaction at 23–27 °C until the reaction is complete. Take 1 mL samples at 0, 10, 20, 30, 40, 50, and 60 min, filter through a 0.22 µm filter membrane, and determine the 6PPD concentration.

[0058] In Example 7, the method for degrading novel p-phenylenediamine pollutants in water showed that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst from Example 1 achieved a degradation rate of 91% for 6PPD within 60 min. This degradation process follows pseudo-first-order reaction kinetics, with an apparent rate constant of 0.038 min. -1 .

[0059] The active species quenching test for the degradation of 6PPD was carried out using the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 1. The test results are as follows: Figure 6 As shown in the figure. Quenching experiments showed that after adding the hole scavenger disodium ethylenediaminetetraacetate (EDTA-2Na) and the superoxide radical scavenger p-benzoquinone (BQ), the degradation rate of 6PPD decreased to 18.8% and 34.7%, respectively, while the degradation rate remained at 60.3% after adding the hydroxyl radical scavenger isopropanol (IPA), confirming that the photogenerated hole h + and superoxide radicals·O2 - It is the dominant active species for degrading 6PPD. This indicates that BiOBr conduction band electrons recombine with Bi2Fe4O9 valence band holes, retaining strong oxidation / reduction capabilities, and that interfacial chemical bonding promotes efficient separation.

[0060] Free radical quenching experiments and band structure analysis confirmed that the BiOBr / Bi2Fe4O9 heterojunction photocatalyst constructed in this invention follows a Z-type charge transfer mechanism. Photogenerated electrons migrate from the conduction band of Bi2Fe4O9 to the valence band of BiOBr and recombine with their holes. Simultaneously, the strongly oxidizing holes in the valence band of Bi2Fe4O9 and the strongly reducing electrons in the conduction band of BiOBr are retained. These electrons directly reduce O2 to generate superoxide radicals (O2). - This efficiently generates superoxide radicals (O2). - The combination of photogenerated holes and photogenerated holes drives the degradation of 6PPD and effectively inhibits the accumulation of the highly toxic intermediate 6PPD-Q. The removal rate of 6PPD can reach 91% within 60 min, and the degradation process conforms to pseudo-first-order reaction kinetics, making it suitable for the deep removal of trace pollutants.

[0061] Example 8 The method for degrading new p-phenylenediamine pollutants in water in Example 8 is basically the same as that in Example 7. The difference between the method for degrading new p-phenylenediamine pollutants in water in Example 8 and that in Example 7 is that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst obtained in Example 2 is used in Example 8.

[0062] In the method for degrading new pollutants such as p-phenylenediamine in water in Example 8, the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 2 showed a degradation rate of 73% for 6PPD within 60 min, which was lower than the 91% of Example 1. This indicates that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst exhibits optimal activity when the mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst is 35%.

[0063] Example 9 The method for degrading new p-phenylenediamine pollutants in water in Example 9 is basically the same as that in Example 7. The difference between the method for degrading new p-phenylenediamine pollutants in water in Example 9 and that in Example 7 is that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst obtained in Example 3 is used in Example 9.

[0064] In the method for degrading new pollutants such as p-phenylenediamine in water in Example 9, the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 3 showed a degradation rate of 84% for 6PPD within 60 min, which was lower than that of Example 1. This indicates that excessive BiOBr will lead to poor coverage of active sites and interface contact of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst.

[0065] Examples 10-12 The methods for degrading new p-phenylenediamine pollutants in water in Examples 10-12 are basically the same as those in Example 7. The difference between the methods for degrading new p-phenylenediamine pollutants in water in Examples 10-12 and those in Example 7 is that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst obtained in Example 4 is used in Example 10. Example 11 uses the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst obtained in Example 5; Example 12 uses the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst obtained in Example 6.

[0066] Comparative Example 1 The preparation method of BiOBr in Comparative Example 1 includes the following steps: 0.5 mmol of Bi(NO3)3·5H2O and 0.5 mmol of KBr were dissolved in 30 mL of ethanol, stirred for 30 min, and then transferred to a 50 mL high-pressure reactor. The mixture was then solvothermal treated at 160 °C for 12 h. The product was washed and dried to obtain pure-phase BiOBr nanoflower-like microspheres.

[0067] Comparative Example 2 The preparation method of Bi2Fe4O9 in Comparative Example 2 includes the following steps: 1.0 mmol of Bi(NO3)3·5H2O and 2.0 mmol of Fe(NO3)3·9H2O were dissolved in 40 mL of deionized water and magnetically stirred for 30 min to form a mixed solution. The pH was adjusted to 10 by slowly adding 2.0 mol / L NaOH solution while stirring, and stirring was continued for 1 h to obtain a brown precipitate. The brown precipitate and mother liquor were transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature. The product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain pure phase Bi2Fe4O9 particles.

[0068] Comparative Example 3 The preparation method of the BiOBr / Bi2Fe4O9 catalyst of Comparative Example 3 includes the following steps: 0.0525 g of BiOBr and 0.0975 g of Bi2Fe4O9 were weighed and ground and mixed evenly in a mortar to obtain a BiOBr / Bi2Fe4O9 catalyst. The mass fraction of BiOBr in the obtained BiOBr / Bi2Fe4O9 catalyst was 35%.

[0069] Comparative Example 4 The preparation method of the g-C3N4 / BiOBr composite material of Comparative Example 4 includes the following steps: Preparation of S1 and g-C3N4: Weigh 5 g of melamine and place it in a crucible. Heat the crucible to 550 °C at 2.5 °C / min in a muffle furnace and hold for 4 h. After natural cooling, grind to obtain light yellow g-C3N4 powder.

[0070] S2, preparation of g-C3N4 / BiOBr composite material: 0.1 g of g-C3N4 was dispersed in 30 mL of ethylene glycol, sonicated for 30 min, and then 0.15 mmol of Bi(NO3)3·5H2O and 0.15 mmol of KBr were added. After stirring for 30 min, the mixture was transferred to a high-pressure reactor and solvothermal reacted at 160 ℃ for 12 h. After washing and drying, g-C3N4 / BiOBr composite material was obtained, wherein the mass fraction of BiOBr in g-C3N4 / BiOBr composite material was 35%.

[0071] Comparative Example 5 The method for degrading new p-phenylenediamine pollutants in water in Comparative Example 5 is basically the same as that in Example 7. The difference between the method for degrading new p-phenylenediamine pollutants in water in Comparative Example 5 and that in Example 7 is that the pure phase BiOBr nanoflower-like microspheres of Comparative Example 1 are used as catalyst in Comparative Example 5.

[0072] In Comparative Example 5, the method for degrading novel paraphenylenediamine (PPD) pollutants in water showed that pure-phase BiOBr nanoflower-like microspheres achieved a removal rate of 45% for 6 PPD within 60 min, and the degradation process followed pseudo-first-order reaction kinetics with an apparent rate constant of 0.008 min. -1 The value is significantly lower than that of Example 7.

[0073] Comparative Example 6 The method for degrading new p-phenylenediamine pollutants in water in Comparative Example 6 is basically the same as that in Example 7. The difference between the method for degrading new p-phenylenediamine pollutants in water in Comparative Example 6 and that in Example 7 is that the pure phase Bi2Fe4O9 particles of Comparative Example 2 are used as catalyst in Comparative Example 6.

[0074] In Comparative Example 6, the method for degrading novel paraphenylenediamine pollutants in water showed that pure-phase Bi₂Fe₄O₉ particles achieved a removal rate of only 32% for 6 PPD within 60 min. The degradation process approximately followed zero-order reaction kinetics, with an apparent rate constant of 0.006 min⁻¹. -1 The value is significantly lower than that of Example 7.

[0075] Comparative Example 7 The method for degrading new p-phenylenediamine pollutants in water in Comparative Example 7 is basically the same as that in Example 7. The difference between the method for degrading new p-phenylenediamine pollutants in water in Comparative Example 7 and Example 7 is that the BiOBr / Bi2Fe4O9 catalyst of Comparative Example 3 is used as the catalyst in Comparative Example 7.

[0076] In the method for degrading new pollutants such as p-phenylenediamine in water in Comparative Example 7, the removal rate of 6PPD by the BiOBr / Bi2Fe4O9 catalyst within 60 min was only 48%, which was lower than that in Example 1. This indicates that the in-situ construction of heterojunctions in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention is beneficial to the formation of a tight interface and efficient charge transfer.

[0077] Comparative Example 8 The method for degrading new p-phenylenediamine pollutants in water in Comparative Example 8 is basically the same as that in Example 7. The difference between the method for degrading new p-phenylenediamine pollutants in water in Comparative Example 8 and that in Example 7 is that the g-C3N4 / BiOBr composite material of Comparative Example 4 is used as a catalyst in Comparative Example 8.

[0078] In the method for degrading new pollutants such as p-phenylenediamine in water in Comparative Example 8, the g-C3N4 / BiOBr composite material achieved a removal rate of 78% for 6PPD within 60 minutes, which is lower than that in Example 1. This indicates that the bandgap matching between Bi2Fe4O9 and BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention is better, and the heterojunction charge separation efficiency is higher.

[0079] Comparative Example 9 The preparation method of the HHCN / BiOBr composite photocatalyst of Comparative Example 9 includes the following steps: 5.0 g of melamine was mixed with 1.0 g of SiO2 nanospheres (particle size 200 nm), ground evenly, and then placed in a covered alumina crucible. The mixture was heated to 550 °C at a rate of 2.5 °C / min in a muffle furnace and held at this temperature for 4 h. After naturally cooling to room temperature, the resulting yellow lumps were ground into powder and dispersed in 100 mL of 2.0 mol / L NaOH solution. The powder was stirred at 80 °C for 12 h to etch and remove the SiO2 template. The product was centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the HHCN precursor.

[0080] 0.10 g of the obtained HHCN precursor was weighed and dispersed in 30 mL of ethylene glycol, and sonicated for 30 min. Then, 0.15 mmol of Bi(NO3)3·5H2O and 0.15 mmol of KBr were added, and stirring was continued for 30 min to form a homogeneous suspension. The resulting homogeneous suspension was transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reactor and reacted solvothermically at 160 °C for 12 h. After the reaction was completed, the reaction product was cooled, centrifuged, washed three times each with deionized water and ethanol, and dried at 60 °C for 12 h to obtain the HHCN / BiOBr composite photocatalyst.

[0081] In the HHCN / BiOBr composite photocatalyst of Comparative Example 9, the thickness of BiOBr nanosheets is 10-20 nm, HHCN maintains a hollow hierarchical porous morphology, and BiOBr nanosheets are discontinuously attached to the surface of HHCN to form a tight heterojunction interface. The mass fraction of BiOBr in the obtained HHCN / BiOBr composite photocatalyst is 35%.

[0082] The methods for degrading novel pollutants such as p-phenylenediamine in water in Examples 7 and 9-12 respectively employed the BiOBr / Bi2Fe4O9 heterojunction composite photocatalysts from Examples 1 and 3-6. Figure 7 As can be seen, the degradation rates of Examples 7 and 9-12 are all significantly higher than 60%, with the degradation rate of Example 7 being significantly higher than 90%, which is significantly better than that of Examples 9-12. This indicates that the BiOBr mass fraction in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention is 35%, which is the best.

[0083] Examples 9 and Comparative Examples 5-6 respectively used the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of Example 3, the pure-phase BiOBr nanoflower-like microspheres of Comparative Example 1, and the pure-phase Bi2Fe4O9 particles of Comparative Example 2 for 6PPD photocatalytic degradation, with the degradation effects of no light and no catalyst, and with light and no catalyst, serving as controls. Figure 8 It can be seen that 6PPD hardly degrades under light-free and catalyst-free conditions; under light-irradiated but catalyst-free conditions, although 6PPD degrades, the degradation rate is extremely low, indicating that light irradiation is an important condition for the degradation of 6PPD. Pure-phase BiOBr nanofloral microspheres and pure-phase Bi2Fe4O9 particles exhibit higher degradation rates for 6PPD, indicating that both can catalyze the visible light degradation of 6PPD. The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst in Example 3 shows significantly better degradation performance of 6PPD than pure-phase BiOBr nanofloral microspheres and pure-phase Bi2Fe4O9 particles, demonstrating that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of this invention can significantly improve the separation efficiency of photogenerated carriers, enhance visible light response, and effectively promote the generation of active species, thereby achieving efficient degradation of 6PPD.

[0084] Using the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst from Example 1, 6 PPD of photocatalytic degradation was carried out under initial pH conditions of 3, 5, 7, 9, and 11, respectively. The degradation effects are as follows: Figure 9As shown in the figure, the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention can effectively catalyze the visible light degradation of 6PPD under both acidic and alkaline conditions, but its activity is highest under neutral conditions. It matches the pH range of natural water bodies and has good stability, making it suitable for the deep removal of new pollutants such as 6PPD in water.

[0085] Under the same degradation conditions, 6PPD was degraded by visible light catalytically using different precursor composite systems. The composite systems used included g-C3N4 / BiOBr composite system, HHCN / BiOBr composite system, BiOBr / Bi2Fe4O9 composite system, ZnO / BiOBr composite system, Mn / BiOBr composite system with Mn contents of 1%, 3%, 5%, 7%, and 10%, Fe / BiOBr composite system with Fe contents of 1%, 3%, and 5%, Cd / BiOBr composite system with Cd contents of 1%, 3%, and 5%, and La-modified La / BiOBr composite system. The degradation of 6PPD under photocatalytic conditions and the degradation of 6PPD under photocatalytic conditions were used as controls. The g-C3N4 / BiOBr composite system used was prepared using the same method as the g-C3N4 / BiOBr composite material in Comparative Example 4, while the HHCN / BiOBr composite system used was prepared using the same method as the HHCN / BiOBr composite photocatalyst in Comparative Example 9.

[0086] The visible light photocatalytic degradation efficiency of 6PPD by different precursor composite systems is as follows: Figure 10 As shown, under the same experimental conditions, the catalyst obtained by combining Bi₂Fe₄O₉ as a precursor with BiOBr exhibits significantly higher degradation efficiency for 6PPD than other composite systems such as the g-C₃N₄ / BiOBr composite system, HHCN / BiOBr composite system, and ZnO / BiOBr catalytic system. This result indicates that Bi₂Fe₄O₉ and BiOBr have a suitable band structure matching relationship and close interfacial contact, which is beneficial for constructing an efficient built-in electric field and promoting the spatial separation of photogenerated electron-hole pairs, thereby significantly improving the photocatalytic oxidation capacity. Therefore, using Bi₂Fe₄O₉ as the optimal precursor, the BiOBr / Bi₂Fe₄O₉ heterojunction composite photocatalyst constructed by subsequently synthesizing the Bi₂Fe₄O₉ precursor via co-precipitation-hydrothermal method, followed by in-situ growth of BiOBr nanosheets via solvothermal method, demonstrates even higher visible light photocatalytic degradation efficiency for 6PPD.

[0087] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst prepared in Example 1 was reused five times under the same conditions. After each reaction, the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst was centrifuged and recovered, washed with deionized water, and then subjected to the degradation of new pollutants such as p-phenylenediamine in water. The results showed that after five cycles, the removal rate of 6PPD by the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst remained above 88% within 60 min. The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst maintained a high degradation efficiency even after multiple uses, indicating that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention has good photochemical stability and reusability.

[0088] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst prepared in Example 1 was placed in distilled water at pH 7 and sonicated for 1 h. After filtration, the concentrations of Bi and Fe ions in the filtrate were determined using inductively coupled plasma optical emission spectrometry (ICP-OES). The results showed that Bi... 3+ and Fe 3+ The leaching concentrations were all below 0.5 mg / L, indicating that the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of the present invention has good structural stability in water, low metal ion dissolution, and low risk of secondary pollution.

[0089] The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of this invention constructs a tight heterojunction interface through in-situ growth, promoting the spatial separation of photogenerated electrons and holes. Simultaneously, the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst retains the strong oxidizing and reducing capabilities of both BiOBr and Bi2Fe4O9 through a Z-type charge transfer mechanism. By controlling the mass ratio of BiOBr to Bi2Fe4O9 in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, optimal light absorption and carrier separation efficiency are achieved. The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst of this invention exhibits high catalytic activity under near-neutral conditions, making it suitable for the removal of novel phenylenediamine pollutants in real natural aquatic environments. Furthermore, this BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst maintains high degradation efficiency even after multiple cycles of use, indicating its good structural stability and reusability, and demonstrating its application potential in the deep treatment of novel pollutants in aquatic environments.

Claims

1. A method for preparing a BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, characterized in that, Includes the following steps: S1: Dissolve the first bismuth source and iron source in a solvent, perform the first reaction, and then dry to obtain the Bi2Fe4O9 precursor; S2: Disperse the Bi2Fe4O9 precursor obtained in S1 in an alcohol solvent, add the second bismuth source and bromine source, and perform the second reaction to obtain the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst.

2. The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst according to claim 1, characterized in that, S1 The first bismuth source includes bismuth nitrate pentahydrate, the iron source includes ferric nitrate nonahydrate, the molar ratio of the first bismuth source to the iron source is 1:(1.5~2.5); the molar volume ratio of the first bismuth source to the solvent is 1 mmol:(30~50) mL; the solvent is water.

3. The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst according to claim 1, characterized in that, S1 further includes adding an alkaline solution to adjust the pH to 10 after dissolving the first bismuth source and the iron source in the solvent and continuing to stir for 1 h. The alkaline solution includes a sodium hydroxide solution with a concentration of 2-7 mol / L. The temperature of the first reaction is 160-180 °C and the time is 12 h. The drying temperature is 60 °C and the time is 12 h.

4. The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst according to claim 1, characterized in that, The alcohol solvent in S2 includes ethylene glycol; the bromine source includes at least one of potassium bromide, sodium bromide or ammonium bromide; the mass-to-volume ratio of the Bi2Fe4O9 precursor obtained in S1 to the alcohol solvent is 0.15 g: 30 mL.

5. The preparation method of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst according to claim 1, characterized in that, S2 The second bismuth source includes bismuth nitrate pentahydrate; the molar ratio of the second bismuth source to the bromine source is 1:1; each (0.1-0.2) g of the Bi2Fe4O9 precursor corresponds to (0.05-1.0) mmol of the second bismuth source; the temperature of the second reaction is 160℃ and the time is 12 h.

6. A BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst as described in any one of claims 1 to 5, characterized in that, In the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst, tetragonal BiOBr nanosheets are discontinuously attached to the surface of orthorhombic Bi2Fe4O9 particles to form a Z-shaped heterojunction. The BiOBr nanosheets exist in the form of nanoflower-like microspheres with a thickness of 10–20 nm. The particle size of the Bi2Fe4O9 particles is 200–500 nm. The Bi2Fe4O9 particles and BiOBr nanosheets are bonded by Bi-O-Fe chemical bonds. The mass fraction of BiOBr in the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst is 10–75%.

7. The application of the BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst as described in claim 6 in the catalytic degradation of novel phenylenediamine pollutants in water, characterized in that, The new pollutants in the p-phenylenediamine class include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine.

8. A method for degrading novel pollutants such as p-phenylenediamine in water, characterized in that, Includes the following steps: The BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst as described in claim 6 is added to the water body to be treated, and the photocatalytic reaction is carried out under visible light conditions.

9. The method for degrading new pollutants of p-phenylenediamine in water according to claim 8, characterized in that, The novel pollutants of the p-phenylenediamine class include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine; the temperature of the photocatalytic reaction is 23–27 °C; the light source for the visible light is a 300 W xenon lamp, and the wavelength of the visible light is >420 nm.

10. The method for degrading new pollutants of p-phenylenediamine in water according to claim 8, characterized in that, 20–50 mg of BiOBr / Bi2Fe4O9 heterojunction composite photocatalyst was added to every 100 mL of the water to be treated; the concentration of p-phenylenediamine-type new pollutants in the water to be treated was 10 mg / L.

Citation Information

Patent Citations

  • Preparation and application of coordination-assisted oxygen vacancy regulated 2D / 2D black BiOBr / white BiOBr homojunction catalyst

    CN121082296A

  • Preparation method and application of BiOBr / TiO2 composite material

    CN122057538A